2004
DOI: 10.1038/sj.eye.6700720
|View full text |Cite
|
Sign up to set email alerts
|

Calculated tumour volume as a prognostic parameter for survival in choroidal melanomas

Abstract: Purpose Tumour diameter, tumour height, and tumour volume are considered important prognostic indicators of survival in choroidal melanomas. In this study, we investigated the prognostic impact on survival of the easily calculated volume estimate based on the assumption of a half-rotation ellipsoid. Methods The largest tumour diameter and tumour height were measured by ultrasound A-and B-scan in 93 patients with choroidal melanoma. Tumour volume was calculated by the half volume of a rotation ellipsoid formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 23 publications
(31 reference statements)
0
37
0
Order By: Relevance
“…The size of the haemangioma was estimated by assuming a rotational ellipsoid, as described previously, 6 in which the volume is calculated by the formula: Estimated Volume ¼ 4pðx:y:zÞ 3…”
Section: Size Of Haemangiomasmentioning
confidence: 99%
See 1 more Smart Citation
“…The size of the haemangioma was estimated by assuming a rotational ellipsoid, as described previously, 6 in which the volume is calculated by the formula: Estimated Volume ¼ 4pðx:y:zÞ 3…”
Section: Size Of Haemangiomasmentioning
confidence: 99%
“…Linear measurement of an orbital mass in three orthogonal dimensions allows an estimation of the volume. 6 The spectrum of velocity within orbital capillary haemangiomas and the changes of velocity during tumour growth and involution are, however, unreportedFas are the temporal changes in dimensions of such lesions.…”
Section: Introductionmentioning
confidence: 99%
“…2 A Cox regression multivariate model that combined LBD (mean 13 mm, range 3-25) and tumour height (mean 7.8 mm, range 1-20), fitted to survival data significantly better (P ¼ 0.0031, difference between models; Table 1) than a model based on tumour volume as calculated by Richtig et al 1 Of models that included only one size parameter (LBD, height, and volume), the one based on LBD fitted to the survival data best and was superior to the one based on volume (P ¼ 0.020, Table 1). …”
Section: Sir Calculated Tumour Volume As a Prognostic Parameter For mentioning
confidence: 99%
“…1 They answered in the positive and also suggested that tumour volume be calculated in daily routine.…”
Section: Sir Calculated Tumour Volume As a Prognostic Parameter For mentioning
confidence: 99%
“…We can therefore plot a 2D graph which represents our pr ility nsity function [9]. The integral which calculates the probability density function is calculated between two points, in obab de this case, the diameter of a cancer cell [10].…”
Section: Probability Densitymentioning
confidence: 99%